2008
DOI: 10.2522/ptj.20070296
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Functional Walking Distance and Health-Related Quality of Life After Gastric Bypass Surgery

Abstract: Improved functional capacity was associated with enhanced HR-QOL. At 6 months, walking distances remained 75% of those for age-matched peers who had normal weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 34 publications
4
50
0
3
Order By: Relevance
“…A prospective 1-year study by Maniscalco et al [21] showed an improvement of the distance walked in six minutes (6MWD) from 475.7 to 626.3 meters in 15 female morbidly obese patients 1 year after laparoscopic adjustable gastric banding. Tompkins J et al [22] confirmed these results and added normative values, namely presurgical walking distance was 55% of normative values and improved up to 75% six months after the operation. Both studies conclude that functional capacity improves because the six minute walking distance improves.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…A prospective 1-year study by Maniscalco et al [21] showed an improvement of the distance walked in six minutes (6MWD) from 475.7 to 626.3 meters in 15 female morbidly obese patients 1 year after laparoscopic adjustable gastric banding. Tompkins J et al [22] confirmed these results and added normative values, namely presurgical walking distance was 55% of normative values and improved up to 75% six months after the operation. Both studies conclude that functional capacity improves because the six minute walking distance improves.…”
Section: Introductionsupporting
confidence: 70%
“…It is known that walking distance is reduced in obese patients compared to lean subjects [44]. According to Tompkins J et al [22], bariatric surgery leads to an improvement up to 75% of normative values six months after the operation. Indeed, weight loss (especially % body fat) makes walking less exhausting, which can be noticed in our results by a decreased rating of perceived exertion and heart frequency at the end of the test.…”
Section: Functional Capacitymentioning
confidence: 99%
“…In addition, Maniscalco et al [15] showed that 1 year after GBS, a significant increase in aerobic exercise capacity was associated with sustained weight loss. The relationship between improvement in aerobic fitness and weight loss was confirmed by Tompkins et al [16], following morbidly obese patients 3 and 6 months after GBS.…”
Section: Introductionmentioning
confidence: 69%
“…Bariatric surgery has been found to improve the distance walked during the six minute walk test (6MWT) [4][5][6]. One of the purposes of this study was to find out whether this could be shown in a Swedish population of women.…”
Section: Introductionmentioning
confidence: 95%